PENGEMBANGAN MEDIA CERITA GELOMBANG ELEKTROMAGNETIK MELALUI MOBILE LEARNING DENGAN SISTEM OPERASI ANDROID - Ishak, Ghina Afifa; Astra, I Made; Permana, A. Handjoko; Azizah, Nur; Widyanirmala, Widyanirmala; Nugraha, Aditiya; Rizki P, Ruhiyat (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
Learning physics requires the media to make physics more interesting to be studied, for it made research that aims to produce an instructional media stories of electromagnetic waves through the mobile learning with the android operating system as supporting media in learning physics. The method used is research and development. This application is validated by using questionnaires filled out by the subject matter experts and media experts. It was also tested empirically by the teacher, then tested to students. The average value of the test results of the questionnaire matter experts about this media of 87.5%, the average percentage of test media expert at 79.39%, 77.39% of the teacher, and the percentage of student responses to the application amounted to 79.79% are interpreted very well. Based on the research results, it can be concluded that the media stories electromagnetic waves with the android operating system can be used as a medium of learning support physics. Keywords: Electromagnetic Waves, Mobile Learning, Android.